COMPLEX GEOLOGICAL–GEOPHYSICAL 3D MODEL OF THE CRUST IN THE SOUTHEASTERN FENNOSCANDIAN SHIELD: NATURE OF DENSITY LAYERING OF THE CRUST AND THE CRUST–MANTLE BOUNDARY - V. N. Glaznev; M. V. Mints; O. M. Muravina; A. B. Raevsky; L. G. Osipenko (Геодинамика и тектонофизика)
The complex geophysical 3D model of the Earth's crust and the upper mantle is created for the Archaean Karelian Craton and the Late Palaeoproterozoic accretionary Svecofennian Orogen of the southeastern Fennoscandian Shield with the use of methods of complex inversion of geophysical data based on stochastic description of interrelations of physical properties of the medium (density, P-wave velocity, and heat generation). To develop the model, we use results of deep seismic studies, gravity and surficial heat flow data on the studied region. Numerical solutions of 3D problems are obtained in the spherical setting with an allowance for the Earth's surface topography. The geophysical model is correlated with the regional geological data on the surface and results of seismic CMP studies along 4B, FIRE-1 and FIRE-3-3A profiles. Based on results of complex geophysical simulation and geological interpretation of the 3D model, the following conclusions are drawn. (1) The nearly horizontal density layering of the continental crust is superimposed on the previously formed geological structure; rock differentiation by density is decreasing with depth; the density layering is controlled by the recent and near-recent state of the crust, but can be disturbed by the latest deformations. (2) Temperature variations at the Moho are partially determined by local variations of heat generation in the mantle, which, in turn, are related to local features of its origin and transformation. (3) The concept of the lower continental crust being a reflectivity zone and the concept of the lower continental crust being a layer of high density and velocity are not equivalent: the lower crust is the deepest, high-density element of near-horizontal layering, whereas the seismic image of the reflectivity zone is primarily related to transformation of the crust as a result of magmatic under- and intraplating under conditions of extension and mantle-plume activity. (4) At certain combinations of crustal thickness and temperature at the level of Moho discontinuity, the crust in a platform region can be transformed into eclogites. In this case, the crust–mantle boundary is determined by quantitative proportions of the rocks that underwent eclogitization or escaped this process and by corresponding density and velocity values. (5) High compaction of rocks in the crust under lithostatic loading cannot be explained by «simple» concepts of metamorphism and/or rock compaction, which are based on laboratory studies of rock samples and mathematical simulations; this is an evidence of the existence of additional, quite strong mechanisms providing for reversible changes of the rocks.